2015
DOI: 10.1159/000381182
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Detection Rates of Aneuploidy in High-Risk Pregnancy Using an Approach Based on Nuchal Translucency and Non-Invasive Prenatal Testing: A Cohort Study

Abstract: Objectives: The aim was to investigate aneuploidy detection using an approach based on nuchal translucency (NT) and non-invasive prenatal testing (NIPT). Methods: This was a cohort study including 5,306 high-risk pregnancies with NT measurements and chorionic villus samples (CVS) tested for full karyotype. Results: The fetal karyotype was normal in 4,172 (78.6%) cases and abnormal in 1,134 (21.4%), including 1,009 with a likely clinically significant adverse outcome. Universal CVS with full karyotyping would l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 50 publications
1
12
0
1
Order By: Relevance
“…Based on the current data and literature review, we suggest that not only an NT ≥3.5 mm, but also an NT ≥3.0 mm could be considered as an indication for invasive prenatal testing because the frequency of chromosome aberrations seems to be very high (in the presented cohort 1:7.4 and according to the literature at least 1:14 7 ). Our results support the previous studies of both Khalil et al and Maya et al, who suggested that invasive testing should be offered in case of a fetal NT ≥3.0 mm 9,37 . If NIPT is offered as the first test, then these women may experience a longer period of anxiety (while waiting for a definitive result) because every abnormal NIPT result requires subsequent confirmatory diagnostic testing.…”
Section: Discussionsupporting
confidence: 89%
“…Based on the current data and literature review, we suggest that not only an NT ≥3.5 mm, but also an NT ≥3.0 mm could be considered as an indication for invasive prenatal testing because the frequency of chromosome aberrations seems to be very high (in the presented cohort 1:7.4 and according to the literature at least 1:14 7 ). Our results support the previous studies of both Khalil et al and Maya et al, who suggested that invasive testing should be offered in case of a fetal NT ≥3.0 mm 9,37 . If NIPT is offered as the first test, then these women may experience a longer period of anxiety (while waiting for a definitive result) because every abnormal NIPT result requires subsequent confirmatory diagnostic testing.…”
Section: Discussionsupporting
confidence: 89%
“…33 Incorporating a NT threshold into the decision algorithm for invasive testing will reduce this proportion, with a recent cohort study demonstrating that when a CVS is prompted by either an abnormal cfDNA result or a NT of 3 mm or greater, only 5.2% of significant abnormalities would not be identified. 34 As noted earlier, our institutional policy is to offer a CVS when the NT is >3.5 mm. In this study, for those abnormal CVS results that would not have been detected by cfDNA testing, applying either this lower NT threshold of ≥ 3 mm or the local standard of 3.5 mm would have failed to identify only five pathogenic fetal karyotypic anomalies overall, representing 1.7% of all pathogenic CVS results in this series.…”
Section: Discussionmentioning
confidence: 97%
“…Studies that have utilised molecular karyotyping indicate that standard cfDNA testing alone would not identify up to 23.4% of potentially clinically significant karyotypic abnormalities that would otherwise have been identified by combined first trimester screening and invasive testing . Incorporating a NT threshold into the decision algorithm for invasive testing will reduce this proportion, with a recent cohort study demonstrating that when a CVS is prompted by either an abnormal cfDNA result or a NT of 3 mm or greater, only 5.2% of significant abnormalities would not be identified . As noted earlier, our institutional policy is to offer a CVS when the NT is >3.5 mm.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of a recent British study was to investigate aneuploidy detection using an approach based on nuchal translucency (NT) and noninvasive prenatal testing (NIPT) [10]. This was a cohort study including 5306 high-risk pregnancies with NT measurements and chorionic villus samples (CVS) tested for full karyotype.…”
Section: Discussionmentioning
confidence: 99%
“…This was a cohort study including 5306 high-risk pregnancies with NT measurements and chorionic villus samples (CVS) tested for full karyotype. A policy of NIPT for increased-risk cases and CVS with full karyotype if the NT was C3.0 mm reduced the risk of miscarriage, yet still identified 95 % of clinically significant aneuploidy [10].…”
Section: Discussionmentioning
confidence: 99%